Estudo etnofarmacológico de espécies vegetais empregadas em crianças no município de São Luís, Maranhão, Brasil - FERREIRA, Tálison Taylon Diniz (2018)
The World Health Organization has stimulated the use of plants for medicinal purposes, provided that its therapeutic efficacy and the safety of its use are proven. In this sense, ethnopharmacological studies have provided important subsidies, making possible the evaluation of the therapeutic resources used by the population. Highlighting in vitro toxicological studies, which determine the toxic potential of products obtained from plants. Thus, the objective of this study was to carry out an ethnopharmacological survey to identify plant species used in children in the municipality of São Luís, capital of the state of Maranhão, Brazil; as well as to carry out toxicity tests on hydroalcoholic extracts of the most mentioned plant species of therapeutic use in the study population, aiming to contribute effectively in the rational use of plants for medicinal purposes and in the actions of Pharmacovigilance. A total of 227 children’s companions (0 to 12 years of age) in care in public health institutions of Primary Health Care, being verified a prevalence of 86.34% of the use of plants for medicinal purposes in children, of which the predominant majority were females. The age of the children's companions ranged from 18 to 82 years, with a predominance of the age group from 28 to 37 years. In the study sample, it was observed a predominance of income less than 02 (two) minimum wages and that the majority of respondents presented at least a High School. The most commonly used therapeutic categories were: diseases of the digestive system, diseases of the respiratory system and Symptoms, signs and abnormal clinical and laboratory findings, not elsewhere classified. The most cited plant species: Lippia alba (Mill) N. E. Brown and Cymbopogon citratus (DC) Stapf indicated as a soothing, Plectranthus barbatus Andrews e Citrus sinensis (L.) Osbeck for the treatament of colic and Mentha piperita L. indicated for the treatment of influenza. Most respondents do not recognize dangers in their use. Among all the analyzed extracts, it was evidenced that the Lippia alba extract (EHLA) was highlighted, since by the test of Artemia salina it was considered toxic and by the MTT cell viability method GM07492A cells showed decreased cell viability. The confirmation of the extensive therapeutic use of plant species in children makes it necessary to implement Pharmacovigilance Programs in Phytotherapy, with emphasis on educational actions alerting the population to the risks and dangers associated with empirical use